Time-dependent wave packet and quasiclassical trajectory study of the C(3P)+OH(X 2?)?CO(X 1?+)+H(2S) reaction at the state-to-state level - Bulut, Niyazi; Zanchet, Alexandre; Honvault, Pascal; Bussery-Honvault, Beatrice; Banares, Luis (Amer Inst Physics, 2009)
The first calculations of state-to-state reaction probabilities and product state-resolved integral cross sections at selected collision energies (0.05, 0.1, 0.5, and 1.0 eV) for the title reaction on the ab initio potential energy surface of [Zanchet J. Phys. Chem. A 110, 12017 (2006)] with the OH reagent in selected rovibrational states (v=0-2, j=0-5) have been carried out by means of the real wave packet (RWP) and quasiclassical trajectory (QCT) methods. State-selected total reaction probabilities have been calculated for total angular momentum J=0 in a broad range of collision energies. Integral cross sections and state-specific rate coefficients have been obtained from the corresponding J=0 RWP reaction probabilities for initially selected rovibrational states by means of a capture model. The calculated RWP and QCT state-selected rate coefficients are practically temperature independent. Both RWP and QCT reaction probabilities, integral cross sections, and rate coefficients are almost independent of the initial rotational excitation. The RWP results are found to be in an overall good agreement with the corresponding QCT results. The present results have been compared with earlier wave packet calculations carried out on the same potential energy surface.
Keywords: ab initio calculations; atom-molecule reactions; carbon; oxygen compounds; potential energy surfaces; reaction kinetics theory; reaction rate constants; rotational-vibrational energy transfer; rotational-vibrational states